How I did it - edited by Daniel McGinn
The essays in How I Did It teach and inspire. Pulled directly from the pages of one of the most popular columns in Harvard Business Review, these essays offer firsthand accounts of the most difficult management challenges faced by the men and women who occupy the corner office. It's the next best thing to sitting down and talking face-to-face with these corporate leaders